Primary Structure of Chlamydomonas reinhardtii Ribulose 1,5-Bisphosphate Carboxylase/Oxygenase Activase and Evidence for a Single Polypeptide - Roesler, Keith R. (1990)
Immunoblot analysis of ribulose 1,5-bisphosphate carboxylase/oxygenase (rubisco) activase from the green alga Chlamydomonas reinhardtii indicated the presence of a single polypeptide. This observation contrasts with the Spinacea oleracea (spinach) and Arabidopsis thaliana proteins, in which two polypeptide species are generated by alternative pre-mRNA splicing. A Chlamydomonas rubisco activase cDNA clone containing the entire coding region was isolated and sequenced. The open reading frame encoded a 408 amino acid, 45 kilodalton polypeptide that included a chloroplast transit peptide. The presumptive mature polypeptide possessed 62% and 65% amino acid sequence identity, respectively, with the spinach and Arabidopsis mature polypeptides. The Chlamydomonas rubisco activase transit peptide possessed almost no amino acid sequence identity with the higher plant transit peptides. The nucleotide sequence of Chlamydomonas rubisco activase cDNA provided no evidence for alternative mRNA splicing, consistent with the immunoblot evidence for only one polypeptide. Genomic DNA blot analysis indicated the presence of a single Chlamydomonas rubisco activase gene. In the presence of spinach rubisco activase, a lower extent and rate of activation were obtained in vitro with Chlamydomonas rubisco than with spinach rubisco. We conclude Chlamydomonas rubisco activase comprises a single polypeptide which differs considerably from the higher plant polypeptides with respect to primary structure.